The value of green certification in the Singapore housing market - FESSELMEYER, Eric (Institutional Knowledge at Singapore Management University, 2018)
In Singapore, a real estate developer sells new apartments in the same high-rise development before and after obtaining green certification. This allows the use of within-development variation in prices over time to measure the effect of green certification on housing prices, controlling for differences across developments. I find that green certification increases prices by around 3%, suggesting that buyers value certification, possibly because it signals the presence of less-salient green features. Moreover, the effect of certification is biggest for developments that receive the lowest green rating, which likely have fewer green features and are thus less obviously green.